Kenya's initiatives in elephant fertility regulation and population control techniques - Joyce Poole (Pachyderm)
During the last two decades, Kenya's elephant population was reduced from 170,000 to 24,000 by poaching. As a result of the 1989 ivory trade ban and increased protection efforts by the Kenya Wildlife Service, the illegal killing of elephants has now essentially stopped. The Service is opposed to culling of elephants and is embarking on a programme of research and development to produce humane methods of elephant population control.